A Problem with Nonlocal Conditions for Partial Differential Equations with Variable Coefficients - Vlasii, O. D.; Ptashnik, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We establish conditions for the unique solvability of a problem for partial differential equations with coefficients dependent on variables t and x in a rectangular domain with nonlocal two-point conditions with respect to t and local boundary conditions with respect to x. We prove metric statements related to lower bounds of small denominators appearing in the course of solution of the problem.